Prevalence and pathophysiology of hypokalemia among adult patients with dengue viral infection - Kaitwatcharachai, Charoen; Namasae, Pongpot (Journal of the Nephrology Society of Thailand, 2022)
Background: Dengue viral infection (DVI) is one of the major public health problems in Thailand and many parts of the world. Renal complications and electrolyte imbalances in DVI have reportedly increased. Even though the prevalence of hypokalemia is common, the mechanisms of hypokalemia remain uncertain. Methods: This study employed a retrospective cross-sectional design to investigate admitted patients with DVI at the Division of Medicine, Hat Yai Hospital, Songkhla from 2011 to 2016. This investigation included patients who were 1) ≥15 years 2) admitted at the Internal Medicine Division with DVI dependence on clinical appearances and confirmed by either dengue NS1 antigen or IgM antibody to dengue infection. Patients with pre-existing renal disease and prescribed diuretics were excluded from this study. Results: This study included 383 patients. The mean serum potassium concentration was 3.75±0.53 mEq/L. and hypokalemia developed among 129 patients (33.7%). Hypokalemia was mild and moderate among 121 (93.8%) and 8 (6.25) patients, respectively. This study demonstrated that age, clinical manifestations, and virus serotypes did not differ between hypokalemia and nonhypokalemia cases. Hypokalemia occurred more frequently among females. Six patients with hypokalemia were additionally investigated. Five patients were female and experienced DHF grade I. Interestingly, these 5 patients had urine potassium to creatinine ratio higher than 13 mEq/gCr and all patients had transtubular potassium gradient higher than 3. Conclusion: Hypokalemia was common among adult patients with dengue virus but not associated with severity of illness or clinical manifestations. The proposed mechanism of hypokalemia was due to renal loss.